A protein- and fiber-rich diet with astaxanthin alleviates high-fat diet-induced obesity in beagles - Xue, Jinhua; Lu, Yuanyuan; Zou, Toujun; Shi, Wei; Wang, Shuang; Cheng, Xu; Wan, Juan; Chen, Yun; Wang, Min; Wang, Qingzheng; Yang, Xia; Ding, Mingxing; et al. (Frontiers in Nutrition, 2022)
Background & Aims: Overweight or obesity is one of the most prevalent health burdens in companion pets, and predisposes subjects to a variety of comorbidities and reduced longevity. Dietary management and increased exercise are effective therapeutic options for weight loss but are largely challenged by modern lifestyle and calorie control-triggered malnutrition. Therefore, the aim of this study was to develop a formulated obesity control diet defined as a protein- and fiber-rich diet with astaxanthin and to systemically evaluate its function in weight-loss and metabolic homeostasis in a high-fat diet (HFD)-established obese beagle model. Methods: Obese beagles were induced by a 24-week HFD treatment and then underwent weight-loss programs. Briefly, obese beagles were randomly assigned to two groups and fed a formulated weight-loss diet or control diet. Body weight and body condition scoring (BCS) were analyzed biweekly. Computed tomography (CT), nuclear magnetic resonance imaging (MRI) measurements, and blood and adipose tissue biopsies were collected at 0 and 8 weeks of diet feeding to evaluate the distribution of the adipose tissue. Plasma lipids and adipocyte size were also measured after 8 weeks of weight-loss diet feeding. Adipose RNA samples were subjected to RNA sequencing to determine the global influence of the formulated diet on the whole spectrum of gene panels during canine obesity. Results: Twenty-four weeks of continuous HFD feeding significantly induced obesity in beagles, as evidenced by increased body weight, BCS, abdominal fat mass and serum lipid levels. The obese condition and metabolic disorders of the modeled canine were effectively improved by an 8-week weight-loss diet administration with good palatability. Importantly, we did not observe any side effects during the weight-loss duration. Transcriptional analysis of adipose tissues further supported that a weight-loss diet significantly increased energy metabolism-related pathways and decreased lipid synthesis-related pathways. Conclusions: The prescribed weight-loss diet exhibited profound benefits in canine weight management with good safety and palatability. These findings support effective strategies of nutritional management and supplementation approaches for weight control in companion animals.